New records of Cochylini moths (Lepidoptera: Tortricidae) from the Balkans - Budashkin, Yuriy; Richter, Ignác (Zootaxa, 2021)
In the course of expeditions conducted on the Balkan Peninsula by Ignác Richter in 2004–2019, altogether 45 species of Cochylini moths were collected. The examination of the collected specimens revealed one new species of the genus Aethes: Aethes larissae sp. nov., from the North Macedonia. Additionally, a new subspecies, Aethes kindermanniana macedonica ssp. nov. is described from the North Macedonia too. Phtheochroa amasiana (Ragonot, 1894) and Cochylimorpha erlebachi Huemer & Trematerra, 1997 are recorded from the Balkans for the first time. A male of Aethes eichleri Razowski, 1983 is collected for the first time, and DNA barcoding data of this species was obtained. We established a new synonymy: Aethes eichleri Razowski, 1983 syn. nov. of Aethes francillana (Fabricius, 1794). Illustrations of specimens and photographs of the genitalia of all described taxa are provided.